2013
DOI: 10.1039/c2nr33173j
|View full text |Cite
|
Sign up to set email alerts
|

Wurtzite CuInS2 and CuInxGa1−xS2 nanoribbons: synthesis, optical and photoelectrical properties

Abstract: Single crystalline wurtzite ternary and quaternary semiconductor nanoribbons (CuInS(2), CuIn(x)Ga(1-x)S(2)) were synthesized through a solution-based method. The structure and composition of the nanoribbons were characterized by X-ray diffraction (XRD), high resolution transmission electron microscopy (HRTEM), the corresponding fast Fourier transform (FFT) and nanoscale-resolved elemental mapping. Detailed investigation of the growth mechanism by monitoring the structures and morphologies of the nanoribbons du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
42
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 69 publications
4
42
1
Order By: Relevance
“…The composition of nanoparticle head in the nanoribbons was approximately identified as four elements by EDS, mainly copper, selenium, and sulfur, partially gallium. In our previous work [34], the similar result on the control experiment was achieved. Cu(dedc) 2 was used as precursor in the presence of dodecanethiol and oleylamine, and crystallized Cu 1.75 S (monoclinic, JCPDS No.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The composition of nanoparticle head in the nanoribbons was approximately identified as four elements by EDS, mainly copper, selenium, and sulfur, partially gallium. In our previous work [34], the similar result on the control experiment was achieved. Cu(dedc) 2 was used as precursor in the presence of dodecanethiol and oleylamine, and crystallized Cu 1.75 S (monoclinic, JCPDS No.…”
Section: Resultssupporting
confidence: 78%
“…Very recently, the SSS mechanism proposed by Wang [38] for nanowire growth provided the clear understanding about the state and structure of catalysts, whose exceptional catalytic ability originated from high-density vacancies and fast mobility of cations. Since 2008, Cu 2 S [30,31], Cu 1.94 S [32,33], Cu 1.75 S [34], Ag 2 S [35,36] and Ag 2 Se [37][38][39] nanocrystals have been found to be the effective catalysts in solution synthesis of nanowires for their intrinsic nature of fast ionic conductor. As one of the fast ionic conductors, Cu 1.75 (SSe) lattice also has the high-density vacancies and fast mobility of copper cations in the rigid sublattice of Se 2À and S 2À [38], promoting the dissolution of gallium ions and their diffusion from the surface to the interface, which made Cu 1.75 (SSe) nanoparticles act as host.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therein, most of the of Cu-based ternary chalcogenides, and has a direct band gap (∼2.4 eV). As a p-type semiconductor, the applications of CuGaS 2 nanomaterials were widely explored in the fields of visible and ultraviolet light-emitting devices [10], thin film solar cell [11], electro-optical devices [12], non-linear devices and detectors [13], photocatalysis [14] etc. However, to the best of our knowledge, there are still limited reports on the application of CuGaS 2 in the field of biological and chemical sensing.…”
Section: Introductionmentioning
confidence: 99%
“…However, compared to the common binary chalcogenides, [14] it is still difficult to control the stoichiometry and crystal phase of the ternary and quaternary nanocrystals because of the different reactivity of metal precursors and the complex interactions between the capping molecules and nanocrystals, which may result in the formation of biphasic nanomaterials or heterostructures as the intermediate products. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] As one of the successful examples for preparing CIS nanostructures, the group of Cui reported the epitaxial growth of CIS nanorods on prenucleated Cu 2 S nanodisks, followed by the progressive transformation of the biphasic Cu 2 S-CIS into monophasic CIS nanorods. [24] Recently, the group of Xie reported that preformed CuSe can be used as a self-sacrificial template for preparation of ultrathin CuInSe 2 nanoplates, but the nanoplates showed small sizes with a broad size distribution.…”
mentioning
confidence: 99%